Spectrum of thrombotic complications and their outcomes in Chinese children with primary nephrotic syndrome - Lv, Yan-Li (Ital J Pediatr, 2020)
BACKGROUND: Thromboembolism is a life-threatening, limb-threatening or organ-threatening complication that occurs in patients with primary nephrotic syndrome (NS). There are few studies on the spectrum, complications and outcomes of thrombosis in children with NS. This study aimed to determine the spectrum of thrombosis and its relationship with the nephrotic state, treatment and outcomes in children and adolescents with primary NS. METHODS: The medical records of subjects aged 1–18 years with NS complicated with thromboembolism treated at our centre within the last 26 years were retrieved. Data on the status of NS, site, symptoms and signs, laboratory investigations, diagnosis, treatment, complications and outcomes of thrombosis were collected and reviewed retrospectively. A severe complication was defined as a condition associated with thrombosis requiring a special diagnostic modality to confirm or a specific treatment such as surgical intervention. The outcome of thrombosis was defined as the status of thrombosis, as determined by imaging methods and the functional status with respect to the anatomic sites of thrombosis at the last follow-up. The permanent dysfunction of an organ or limb related to thrombosis was defined as a sequela. RESULTS: We observed thrombosis in 1.4% (27/1995) of subjects with NS during the study period. There were 27 subjects with thrombosis, including 21 males and 6 females. Thrombosis was observed in 51.9% (14/27) of the study participants with steroid resistant NS. Most episodes of thrombosis occurred during the active stage of NS; however, 7.4% of thrombosis cases occurred during the remission of proteinuria. Renal vein thrombosis (33.3%) and pulmonary embolism (25.9%) were the most common types of thrombosis. Among the 17 subjects biopsied, minimal change disease and membranous nephropathy were the two most common findings. Six (22.2%) subjects experienced severe complications or sequelae; 1 had persistent intracranial hypertension, 1 had intestinal perforation, 1 had hypoxemia and pulmonary hypertension, 1 had lameness, 1 had epilepsy, and 1 had an askew mouth due to facial paralysis. In 19 (70.4%) subjects, the symptoms resolved completely or improved without severe complications or sequelae. CONCLUSIONS: Thrombosis mostly occurred in males of school age during the active stage of NS. Renal vein thrombosis and pulmonary embolism were the most common types of thrombosis. In most patients with thrombosis, the symptoms improved completely without complications with standard anticoagulation therapy. However, 22.2% had severe complications or sequelae requiring an advanced diagnostic modality and aggressive treatment.